2021
DOI: 10.1186/s12909-021-02980-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of modified BOPPPS-based SPOC and Flipped class on 5th-year undergraduate oral histopathology learning in China during COVID-19

Abstract: Background Colleges and universities in China have offered courses based on online teaching platforms as required by the Ministry of Education since the beginning of the COVID-19 pandemic. This emergency action was not an expedient measure, but a powerful impetus to improve extant education and implement teaching reform. Oral histopathology is a basic subject in oral medicine education, which combines theory with practice. The course aims to improve the ability of students to observe, think, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 20 publications
(13 reference statements)
0
12
0
2
Order By: Relevance
“…In recent years, the BOPPPS model, which pays more attention to the role of students’ initiatives in the teaching process and fully mobilizes their initiatives in the learning process, has been widely considered in China [ 32 ]. A large amount of the literature has shown the advantages of the BOPPPS model in various fields in health care and medicine [ 33 ], such as clinical medicine [ 34 ], dentistry [ 8 ], and histopathology [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the BOPPPS model, which pays more attention to the role of students’ initiatives in the teaching process and fully mobilizes their initiatives in the learning process, has been widely considered in China [ 32 ]. A large amount of the literature has shown the advantages of the BOPPPS model in various fields in health care and medicine [ 33 ], such as clinical medicine [ 34 ], dentistry [ 8 ], and histopathology [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Author details 1 Department of Mathematics and Information Technology, The Education University of Hong Kong, Hong Kong SAR, China. 2 Faculty of Education, The University of Hong Kong, Hong Kong SAR, China.…”
Section: Supplementary Informationmentioning
confidence: 99%
“…The meta-analysis results of the effectiveness indicator showed that when compared with the LBL group, the SS, KES, CAS, and TS of the BOPPPS group were higher, suggesting that the BOPPPS teaching strategy could stimulate the enthusiasm and interest of medical students, boost Students’ skills and intrinsic motivation in learning; and improve the self-directed learning ability, academic performance ( 6 , 59 ). On the other hand, the BOPPPS teaching strategy with a six-phase framework was adapted to organize and accelerate the teaching cycle as a whole including goal, behavior, learning activity, and evaluation ( 60 ), which help teachers generate innovative teaching ideas and timely adjustment of teaching schedule.…”
Section: Discussionmentioning
confidence: 99%